Complement C1q is associated with neuroinflammation and mediates the association between amyloid-β and tau pathology in Alzheimer’s disease - Fan Guo; Ze-Hu Sheng; Yan Fu; Zhi-Bo Wang; Rong-Ji Xue; Lan Tan; Meng-Shan Tan; Zuo-Teng Wang (Translational Psychiatry)
Abstract Complement C1q initiates the classical complement pathway and becomes activated in Alzheimer’s disease (AD), contributing to the association between amyloid-β (Aβ) and tau pathologies. However, whether C1q influences AD pathology by modulating glial cell communication is unclear. We included 217 participants from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database to explore the associations of cerebrospinal fluid (CSF) C1q with soluble triggering receptor expressed on myeloid cells 2 (sTREM2), glial fibrillary acidic protein (GFAP) and AD biomarkers. Additionally, we incorporated data from 535 participants in the Chinese Alzheimer’s Biomarker and LifestylE (CABLE) study to explore associations. We employed 10,000 bootstrapped iterations of causal mediation analysis to examine the possible mediating role of sTREM2 or GFAP in the relationship between CSF C1q and AD pathology. We found that CSF rather than serum C1q were positively associated with CSF sTREM2, GFAP, Aβ42, phosphorylated-tau (P-tau) and total tau (T-tau) at baseline. CSF C1q was only longitudinally associated with CSF T-tau levels and AD assessment scale-cognitive subscale 13 (ADAS-Cog 13) scores. Mediation analysis demonstrated that Aβ pathology partly mediated the association between CSF C1q and sTREM2 levels, which in turn impacted tau pathology progression. Serum C1q showed a significant association with CSF sTREM2 at baseline as well. Conclusions C1q is associated with CSF sTREM2 and mediates the relationship between Aβ and tau pathologies. This suggests that C1q may play a crucial role in the progression from Aβ pathology to tau pathology.